2 - Variations in Postcolonial Imagination: Reflection on Senghor, Nyerere and Nkrumah - Adesina, Jimi O. (Africa Development, 2022)
This article aims to strengthen contemporary efforts to construct and pursue a pan-African agenda by interrogating the postcolonial imaginings of Léopold Sédar Senghor, Julius Nyerere and Kwame Nkrumah. To counter the present-day tendency to erase and flatten the diversity of this period, the article explores the variations and similarities of the three leaders’ approaches to socialism, pan-African unity, nationhood, economic development, epistemology and democracy. Through this contrast, the article derives some broad lessons for the contemporary period, including the importance of cultivating domestic resources (human, material and financial) rather than being dependent on external forces; the need for countries to construct a macro-vision that coordinates their economic, social and political projects; and the importance of maintaining sovereignty of thought in policy thinking on the continent to effectively break free from the universal, market-based prescriptions that now dominate under neoliberalism.